Sharing of Knowledge: Hambatan Keterlibatan Mahasiswa dalam Diskusi - Yulius Aldo Bima Prasetyo; Tutuk Ari Arsanti (Jurnal Maksipreneur, 2017)
Knowledge sharing is an important process in the development of knowledge, especialy for higher education such as universities. Knowledge sharing process can happen to students in the form of discussion. However, in the process there are several factors that hamper the process of discussion among students. This study aims to find and identify the barriers that exist in the process of discussion. Sources of data are primary obtained initially through observation then through interviews on 17 students of management program. The results of this study indicate the existence of some barriers that inhibit the process of discussion in the classroom. The barriers found in this study are identified as barriers of individual and organizational factors.